Transforming education in a rural ecosystem: school libraries as hubs for teaching-learning innovation - Mdodana-Zide, Lulama; Chimbi, Godsend T. (Frontiers in Education, 2025)
IntroductionAlthough literature shows that libraries can play a significant role in student learning, very little is known about how the availability of libraries can transform rural education ecosystems. This study, therefore, positions libraries as innovative hubs for improving how teachers teach and students learn in rural schools, often incapacitated by resource scarcity in the Eastern Cape province of South Africa.MethodsDeploying the theoretical lens of Todd and Kuhlthau's Model of the School Library as a Dynamic Agent of Learning, this qualitative study explores the potential of school libraries as innovative pedagogical hubs to improve teaching and learning in rural schools. The study adopts a multiple case study design by purposively selecting six schools as research sites in a rural school district of the Eastern Cape in South Africa. Using a sample of 12 teachers, data were collected through semi-structured interviews and processed using content and thematic analyses.ResultsThe findings indicate that school libraries can improve teachers' lesson preparation and learner engagement by encouraging learner-centered environments and curriculum differentiation. Libraries also help mitigate resource inadequacies, enhancing teachers' subject knowledge and pedagogy. By establishing and maintaining functional school libraries as innovative pedagogical hubs, instead of mere repositories of information, school libraries can enhance the quality of teaching and learning in rural schools.DiscussionThe other quintessential findings of this study were that libraries catalyzed learners' self-directed learning and the quest to find more information on the concepts they were learning. This nurtured their critical thinking, creativity, and research skills. The study advocates the development of curriculum policy guidelines that prioritize the availability of school libraries to promote quality teaching and learning in rural education ecosystems.